SAT0129 Antalgic effects of u69593, a kappa agonist, do not implicate adenosine release. (1st June 2001) - Pham, T; Peragut, JC; Rochat, H; Lafforgue, P; Guieu, R
Abstract : Background: There is evidence that endogenous adenosine (ADO) is impicated in the modulation of opiate action in central and peripheral nervous system, via both A1 and A2A receptors. Objectives: However, little is know about the interaction between opioid receptor agonist subtype and ADO release at the supraspinal level. We sought to answer two questions: first, what subtype of opioid receptor is more particularly implicated in the modulation of ADO uptake by the supraspinal central nervous system cells? Second, is there a relationship between the modulation of extracellular ADO concentration by opioid agonist-subtype and the antalgic effects? Methods: We evaluated the effects of caffeine, a non specific ADO receptor antagonist on the hot-plate and tail pinch test latency increase that is induced by i.c.v. administration of oxymorphone hydrochloride, SNC 80 or U69593(respectively μ, ∂ and k agonist). We also evaluated the effects of these opioid receptor agonists on the uptake of ADO by whole brain synaptosomes (HPLC). Results: Tail-pinch test and Hot-plate latencies Opioïds and ADO agonists induce an increase both in tail-pinch test and hot-plate latencies in a dose dependant manner and in the rank order as follows: Oxymorphone hydrochloride > CCPA >SNC80 >CGS21680 = U69593. No increase in tail-pinch test and hot-plate latencies was observed ten minutes after i.c.v injection whatever the drug tested. Opioïds and ADO agonists have synergistic effects when coinjected. The rank order was: CCPA + Oxymorphone > CCPA + SNC80 = CGS21680 + Oxymorphone > CCPA+ U69593 = CGS21680 + SNC80 > CGS21680 + U69593. The increase in latencies induced by Oxymorphone and SNC80 (but not U69593) was partly reversed by coinjection of caffeine. Caffeine alone had no effect on latencies. ADO uptake ADO uptake was evaluate by measuring the decrease in adenosine concentration in the supernatant as a function of time. Oxymorphone hydrochloride at 10 μM increased ADO concentration by a mean of 16, 21 and 25% at times 5, 30, and 60 s respectively. SNC80 (10 μM) increased ADO concentration by 17, 16 and 40% at times 5, 30 and 60 s. At 100 μM, SNC80 increased ADO concentration by 26, 24 and 60% at times 5, 30 and 60 s. U69593 did not significantly modify ADO concentration in the supernatant whatever the dose used. Finally, none of the opioïds tested had a significant effect on ADO uptake at 1 μM concentration. Conclusion: In summary, we found that oxymorphone and SNC80, but not U69593 (respectively μ, ∂ and k agonist) inhibits ADO uptake by brain cells. Furthermore, caffeine which is a non specific ADO receptor antagonist, failed to reverse antalgic effect obtained with U69593 in a acute pain model. These results suggest that the antalgic effects of k opioïd agonist does not implicate ADO release.